2018
DOI: 10.1007/s00216-018-0897-x
|View full text |Cite
|
Sign up to set email alerts
|

Voltammetric and electrogeneration approaches for the assessment of the oxidative drug metabolism

Abstract: In this paper, electrochemical (EC) methods have been proposed to evaluate the oxidative behavior of drugs as rapid, simple, and cheap strategies to predict some metabolic features. Various commercial drugs belonging to different therapeutic families have been assayed to deal with a wide variety of biotransformations and to cover different metabolism extents. First, differential pulse voltammetry has been applied to evaluate the oxidative behavior of drugs. Voltammetric assays have demonstrated to be highly ef… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 29 publications
0
7
0
Order By: Relevance
“…This method has already been used to investigate the electrochemical behaviour of other oxidatively toxified drugs such as paracetamol or diclofenac [51] . Furthermore, a recent study concluded that electrochemical oxidation is a suitable approach for a preliminary investigation of the oxidative behaviour of drug candidates since the profile of generated oxidation products is roughly comparable to in vitro microsomal incubation [52] …”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…This method has already been used to investigate the electrochemical behaviour of other oxidatively toxified drugs such as paracetamol or diclofenac [51] . Furthermore, a recent study concluded that electrochemical oxidation is a suitable approach for a preliminary investigation of the oxidative behaviour of drug candidates since the profile of generated oxidation products is roughly comparable to in vitro microsomal incubation [52] …”
Section: Resultsmentioning
confidence: 99%
“…[51] Furthermore, a recent study concluded that electrochemical oxidation is a suitable approach for a preliminary investigation of the oxidative behaviour of drug candidates since the profile of generated oxidation products is roughly comparable to in vitro microsomal incubation. [52] Figure 5 shows a representative cyclic voltammogram of compound 35 a versus retigabine. The anodic peak potentials, which are marked by dashed lines, indicate that 35 a with an oxidation potential of 633 mV is significantly more oxidationstable compared to retigabine (E p.a.…”
Section: Evaluation Of Oxidizabilitymentioning
confidence: 99%
See 1 more Smart Citation
“…In combination with strides in developing new selective electrosynthetic methodologies that can be applied to drug molecules, this would enable a fully joined‐up approach to discovery, detection and generation of drug metabolites, and scalable synthesis of new analogues to expedite drug discovery. To achieve these grand ambitions of metabolism‐inspired electrosynthesis, further cutting‐edge development of pulse sequences for electrooxidation, engineering advantages for redox cycling and preventing electrode fouling/compound adsorption, microfluidic technologies, and rapid screening technologies are emerging and will all play a role in the wider adoption of electrosynthesis.…”
Section: Perspective On Future Developmentsmentioning
confidence: 99%
“…Our interest in connecting the voltammetric behaviour of drug molecules to their biological properties is derived from our research into the electrochemistry of small molecules [12][13][14] and adverse drug reactions [15,16]. Recent disparate research has found connections between the redox behaviour of a drug and its biological potency [17][18][19] and the oxidation potential and toxicity of MDMA (Ecstasy) derivatives [20,21] and thiobenzamides [22], and voltammetric studies for assessing electrogenerated drug metabolisms [23] as well as a study of xeniobiotics in the environment [24].…”
Section: Introductionmentioning
confidence: 99%